Pattern of Presentation of Neurocutaneous Syndromes in a Tertiary Care Hospital of Bangladesh (Bangladesh Journal of Child Health, 2019)
Background: Neurocutaneous syndromes (NCS) represent a group of central nervous system disorders associated with lesion in the skin, eye and possibly other visceral organs. Various cutaneous manifestations usually appear early in life, progress with time but neurological features generally present at a later age. The objective of this study is to observe the frequency of pattern and presentation of various forms of neurocutaneous syndrome.Methodology: A descriptive cross sectional study was conducted at department of Paediatric Neurology of Bangabandhu Sheikh Mujib Medical University(BSMMU), Dhaka, Bangladesh from March, 2015 to February, 2016. Children (3month to 8 years) with NCS, diagnosed on the basis of standard diagnostic criteria for different NCS were included and compared.Results: Among of 27 children,16 (59.26%) boys, 09(40.74%) girls with neurocutaneous syndrome, mean age of presentation was 38.67±18.57 (range 3 month to 84 months). The various forms of NCS observed were Tuberous sclerosis complex (48.14%), Ataxia telangiectasia (29.62%), Sturge Weber Syndrome (14.81%), Neurofibromatosis1(3.7%) and Linear nevus syndrome (3.7%). In Tuberous sclerosis complex , most common feature was facial angiofibroma ( 92.30%), Hypomelanotic macule (76.90%), Shagreen patch (76.90%). In Ataxia telangiectasia, commonest presentation was ataxia 8(100%) followed by ocular telangiectasia (62.50%). In Sturge weber syndrome, commonest presentation was facial capillary malformation (100%). Neurofibromatosis patient presented with café-au-lait spot (100%). Common systemic manifestations of NCS were found in TSC and those were multicystic kidney disease (30.76%), autism spectrum disorder (15.38%) & attention deficit hyperactivity disorder (7.69%).Conclusion: In our study, the commonest neuro-cutaneous syndrome is tuberous sclerosis complex and it’s cutaneous manifestation is facial angiofibromaBangladesh J Child Health 2019; VOL 43 (1) :15-20